Automatic and label‐free identification of blood vessels in gliomas using the combination of multiphoton microscopy and image analysis. Issue 9 (30th May 2019) - Fang, Na; Wu, Zanyi; Wang, Xingfu; Kang, Dezhi; Li, Lianhuang; Chen, Yupeng; Zheng, Xianying; Cai, Shanshan; Liu, Xueyong; Chen, Zhida; Tu, Haohua; Lin, Yuanxiang; et al.
Abstract: Currently, the targeted treatment of tumor based on the tumor microenvironment is newly developed. Blood vessels are the key parts in the tumor microenvironment, which is taken as a new visible target for tumor therapy. Multiphoton microscopy (MPM), based on the second harmonic generation and two‐photon excited fluorescence, is available to make the label‐free analysis on the blood vessels in human gliomas. MPM can reveal the vascular morphological characteristics in gliomas, including vascular malformation, intense vascular proliferation, perivascular collagen deposition, perivascular lymphocytes aggregation and microvascular proliferation. In addition, the image analysis algorithms were developed to automatically calculate the perivascular collagen content, vascular cavity area, lumen area, wall area and vessel number. Thus, the vascular morphology, the perivascular collagen deposition and intense vascular proliferation degree can be further quantitatively characterized. Compared with the pathological analysis, the combination of MPM and image analysis has potential advantages in making a quantitative and qualitative analyzing on vascular morphology in glioma microenvironment. As micro‐endoscope and two‐photon fiberscope are technologically improved, this combined method will be a useful imaging way to make the real‐time research on the targeting tumor microenvironment in gliomas. Abstract : Multiphoton microscopy combined with customized image processing algorithms is taken as a quick and label‐free tool to analyze the vascular morphology in gliomas. This approach allows the multiphoton microscopy to directly visualize and automatically assess the blood vessels in the unstained glioma tissues. It offers a fundamental proof of reasoning to put the in vivo fiberscopes and multiphoton microendoscopes into clinical use.